Virtual comprehensive higher education search engine - Abdul Wahid, Al- Abrar; Aboubakar Idriss, Hissein; Muhamnad, Muhammad; Ahmad Dahlan, Abdul Rahman (2011)
Malaysian universities or colleges has been one of the main attractive educational destinations to foreigners for the last decade. Malaysian educational institutions are recognized in opening doors of knowledge that fulfill student’s lives with skills, awareness and enthusiasm. There are over 20 public universities and 60 private colleges that offer a complete range of programs leading to highly regarded and internationally recognized qualifications. Despite the vast information made available by these institutions on their websites, majority of potential students face challenges in choosing the right program, courses and university that suits their needs. This research study the innovative method which could be tapped by the educational industries specifically Ministry of Higher Education in using search engine comparator technology assisting potential students in making optimum selection.